Three-dimensional breathable electrode plate and preparation method and application thereof
By applying water-soluble film-forming materials and viscous silica gel on the conductive fabric and dissolved the water-soluble material coating after the viscous silica gel cures, forming a three-dimensional breathable electrode sheet, the skin allergy and signal drift problems caused by commercial Ag/AgCl wet electrodes are solved, and the biocompatibility and signal stability of the electrode sheet are achieved.
Patent Information
- Application Number
- CN202411568783.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-03-11
AI Technical Summary
The existing commercial Ag/AgCl wet electrodes will cause itching and allergic skin when worn for a long time, and the adhesion of silver-plated fabrics will be insufficient, resulting in signal drifting when the detector's body makes movements.
The preparation method of a three-dimensional breathable electrode sheet is adopted, including cleaning the conductive fabric, coating water-soluble film-forming materials and viscous silica gel, and dissolving the water-soluble material coating after the viscous silica gel is completely cured to form a three-dimensional breathable electrode sheet with a breathable network structure.
This method reduces the skin itching, redness, swelling and even allergies caused by the user during long-term wear, ensures the biohistocompatibility of the electrode sheet, makes the electrode sheet comfortable to wear, reduces the wearer's discomfort, and improves the stability of the signal and avoids signal drift.
Smart Images

Figure CN119587036A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of bioelectric dry electrodes, and in particular to a three-dimensional breathable electrode sheet and a preparation method and application thereof. Background Art
[0003] Monitoring cardiovascular physiological characteristics to detect related diseases or potential risks is of great significance to health protection. Electrocardiogram is a visualization of cardiac electrical signals and is a simple but important means of screening and diagnosing cardiovascular diseases.
[0004] However, the commercial Ag / AgCl wet electrodes currently used in professional ECG machines can cause itching and allergies to the user's skin if worn for a long time. Moreover, long-term use or storage can cause the gel to dry and performance to deteriorate, which is not conducive to long-term ECG data collection for patients and affects the accuracy of ECG data. The silver-plated fabric used in commercial dynamic ECG clothing cannot adhere to the skin, and when the subject moves, there will be a signal drift problem. Summary of the invention
[0005] The purpose of the present invention is to provide a three-dimensional breathable electrode sheet and a preparation method thereof, so as to solve the problem that the user's skin may itch and be allergic when wearing the above commercial Ag / AgCl wet electrode for a long time. The purpose of the present invention is also to provide an application of a three-dimensional breathable electrode sheet to solve the problem that the electrode sheet is not sufficiently adherent and causes signal drift when the body of the tester moves.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing a three-dimensional gas-permeable electrode sheet, comprising the following steps:
[0008] S1. Cleaning the conductive fabric;
[0009] S2, uniformly coating the water-soluble film-forming material solution on one side of the conductive fabric, and drying the solution to form a water-soluble material coating on one side of the conductive fabric, thereby obtaining a conductive fabric with a film;
[0010] S3, coating the sticky silica gel on the other side of the conductive fabric with the film, and degassing, so that the sticky silica gel fills the gaps in the conductive fabric; heating and drying, to obtain the silica gel conductive fabric;
[0011] S4, pressing a mesh lining cloth on the other side surface of the silicone conductive fabric; performing curing and drying to completely cure the silicone to obtain a cured conductive fabric;
[0012] S5. Soak the cured conductive fabric in water to completely dissolve the water-soluble material coating, and obtain a three-dimensional breathable electrode sheet after drying.
[0013] In the method for preparing the three-dimensional breathable electrode sheet, the conductive fabric includes one of silver-plated fabric, laser-induced graphene fabric and copper-nickel-plated fabric.
[0014] In the method for preparing the three-dimensional breathable electrode sheet, one side of the conductive fabric is a weft layer, the other side of the conductive fabric is a warp layer, and the weft layer of the conductive fabric is in a twill grid shape.
[0015] In the method for preparing the three-dimensional breathable electrode sheet, in step S3, after degassing, the viscous silicone is scraped flat so that the viscous silicone fills the gaps between the warp layer and the weft layer, and excess viscous silicone is scraped off so that the liquid surface of the viscous silicone is level with the warp layer.
[0016] In the method for preparing the three-dimensional breathable electrode sheet, the coating density of the water-soluble film-forming material solution is 0.35 to 0.45 L / m 2 .
[0017] In the method for preparing the three-dimensional breathable electrode sheet, the water-soluble film-forming material solution comprises a water-soluble film-forming material and a solvent, the water-soluble film-forming material is dissolved in the solvent, and the concentration of the water-soluble film-forming material is 2.5 to 12.5 wt %;
[0018] The water-soluble film-forming material includes one of hydroxypropyl methylcellulose, polyvinyl pyrrolidone, polyacrylic acid and its salts, gelatin and polyethylene glycol, and the solvent includes one of water and ethanol.
[0019] In the preparation method of the three-dimensional breathable electrode sheet, the viscous silica gel includes polybutylene terephthalate-adipate copolymer and medical silicone gel. Calculated by mass percentage, the polybutylene terephthalate-adipate copolymer accounts for 10-30% of the total mass of the viscous silica gel.
[0020] In the method for preparing the three-dimensional breathable electrode sheet, in step S5, the temperature of the water in which the curing conductive fabric is immersed is 95-100°C.
[0021] The present invention also provides a three-dimensional breathable electrode sheet, which is prepared by the above-mentioned method for preparing the three-dimensional breathable electrode sheet.
[0022] The present invention also provides an application of a three-dimensional breathable electrode sheet in a dry ECG electrode, wherein the electrode sheet of the potential sensor is prepared by the above-mentioned method for preparing the three-dimensional breathable electrode sheet.
[0023] A technical solution in the present invention can have the following beneficial effects:
[0024] The preparation method of the three-dimensional breathable electrode sheet is to cover one side of the conductive fabric with a water-soluble material to form a water-soluble material coating, and then cover the other side of the conductive fabric with a sticky silica gel and a lining cloth; after the sticky silica gel is completely cured, the water-soluble material coating is dissolved to obtain a three-dimensional breathable electrode sheet with a breathable network structure. As the water-soluble material coating on one side of the conductive fabric is dissolved, one side of the conductive fabric is exposed, and after contacting the skin, accurate collection of biopotential can be achieved; and the breathable network structure of the conductive fabric can reduce the occurrence of skin itching, redness, swelling, and even allergies during long-term wearing of the user, ensure the bio-tissue compatibility of the electrode sheet, make the electrode sheet comfortable to wear, and reduce the discomfort of the wearer. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a schematic cross-sectional view of a conductive fabric with a film in one embodiment of the present invention;
[0026] Figure 2 is a schematic cross-sectional view of a silicone conductive fabric in one embodiment of the present invention;
[0027] Figure 3 is a cross-sectional schematic diagram of a three-dimensional gas-permeable electrode sheet in one embodiment of the present invention;
[0028] Figure 4 is a schematic diagram of the microstructure of the conductive fabric;
[0029] Figure 5 It is a graph of the water evaporation rate;
[0030] Figure 6 It is the horizontal uniaxial force curve of the vibration motor;
[0031] Figure 7 This is the curve of pigskin contact impedance change under 1.0V power supply;
[0032] Figure 8 This is the curve of pigskin contact impedance change under 1.5V power supply;
[0033] Fig. 9 It is a waveform diagram output by the electrocardiograph when the embodiment 4 and the commercial 3M gel electrode foam adhesive are applied;
[0034] Fig.10 It is the output graph of ECG and respiratory waveform in walking state;
[0035] Fig.11 This is the output graph of ECG and breathing waveforms in the jogging state;
[0036] In the accompanying drawings: weft layer 1, warp layer 2, water-soluble material coating 3, adhesive silica gel 4, lining cloth 5. DETAILED DESCRIPTION
[0037] The technical scheme of the present invention is further illustrated by specific embodiments below. In order to facilitate understanding of the present invention, the present invention is described more comprehensively below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0038] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0040] Please refer to Figures 1 to 11 The present invention provides a method for preparing a three-dimensional gas-permeable electrode sheet, comprising the following steps:
[0041] S1. Cleaning the conductive fabric;
[0042] S2, uniformly coating the water-soluble film-forming material solution on one side of the conductive fabric, and drying the solution to form a water-soluble material coating 3 on one side of the conductive fabric, thereby obtaining a conductive fabric with a film;
[0043] S3, coating the sticky silica gel 4 on the other side of the conductive fabric with the film, and degassing, so that the sticky silica gel 4 fills the gaps in the conductive fabric; heating and drying, to obtain the silica gel conductive fabric;
[0044] S4, pressing a mesh lining cloth 5 on the other side surface of the silicone conductive fabric; performing curing and drying to completely cure the silicone to obtain a cured conductive fabric;
[0045] S5. Soak the cured conductive fabric in water to completely dissolve the water-soluble material coating 3, and obtain a three-dimensional breathable electrode sheet after drying.
[0046] The preparation method of the three-dimensional breathable electrode sheet is as follows: a water-soluble material is covered on one side of the conductive fabric to form a water-soluble material coating 3, and then a sticky silica gel 4 and a lining cloth 5 are covered on the other side of the conductive fabric; after the sticky silica gel 4 is completely solidified, the water-soluble material coating 3 is dissolved to obtain a three-dimensional breathable electrode sheet with a breathable network structure. Since the water-soluble material coating 3 on one side of the conductive fabric is dissolved, one side of the conductive fabric is exposed, and after contacting the skin, accurate collection of biopotential can be achieved; and the breathable network structure of the conductive fabric can reduce the occurrence of skin itching, redness, swelling, and even allergies during long-term wearing by the user, ensure the bio-tissue compatibility of the electrode sheet, make the electrode sheet comfortable to wear, and reduce the discomfort of the wearer.
[0047] The sticky silica gel 4 is filled in the gaps of the conductive fabric to provide adhesion, ensuring that the electrode sheet and the wearer are not easily loosened during exercise, so that the electrode-skin contact interface remains stable, ensuring that the electrode sheet can still collect stable signals during the wearer's exercise.
[0048] The lining cloth 5 serves to increase the strength of the electrode sheet. In practice, when the proportion of the sticky silica gel 4 increases, the strength of the electrode sheet will deteriorate, making it impossible to completely peel the electrode sheet from the solidified plane. After adding the lining cloth 5, the electrode sheet can be prevented from being torn by the interaction of the peeling force of the conductive fabric and the adhesion force of the sticky silica gel 4 when peeling. The mesh on the lining cloth 5 can further increase the air permeability of the electrode sheet.
[0049] The water-soluble material coating 3 plays a role in preventing the viscous silica gel 4 from flowing out from one side of the conductive fabric. When the viscous silica gel 4 is applied, in order to ensure the coating effect, the viscous silica gel 4 has a high water content and a certain fluidity. The water-soluble material coating 3 can be applied to one side of the conductive fabric to prevent the viscous silica gel 4 from flowing out from the gaps of the conductive fabric.
[0050] In step S3, heating and drying are performed to volatilize the moisture of the viscous silica gel 4 and reduce the fluidity of the viscous silica gel 4. In a specific embodiment of the present invention, the heating and drying step in step S3 includes placing the film-bearing conductive fabric coated with the viscous silica gel 4 after degassing in a 30°C drying oven for 15 minutes. The curing and drying step in step S4 includes: placing the silicone conductive fabric after the lining cloth 5 is pressed into a 60°C drying oven for 1 hour to completely cure the viscous silica gel 4, so that the viscous silica gel 4 becomes gel-like and cannot flow. When the viscous silica gel 4 is completely cured, the cured conductive fabric can be placed in water to dissolve the water-soluble material coating 3 and expose the conductive fabric.
[0051] In a specific embodiment of the present invention, step S1 includes: cutting the size of the conductive fabric and performing plasma cleaning. The specific operation of plasma cleaning includes placing the cut conductive fabric in a plasma cleaning machine and cleaning it in an oxygen atmosphere for 120 seconds at a power of 20W.
[0052] The degassing operation may be vacuum degassing, by which bubbles in the viscous silica gel 4 can be eliminated, thereby preventing the bubbles in the viscous silica gel from affecting the collection of biopotential, causing measurement errors, and reducing accuracy.
[0053] In the prior art, laser drilling or water-soluble sacrificial particles are usually used to enhance the air permeability of the electrode sheet. Compared with the preparation method described in the present invention, the laser drilling method will reduce the effective conductive area, and due to the laser thermal effect, the high temperature generated during the laser drilling process can easily reduce the adhesion of the silicone, or even prevent adhesion. In addition, the distribution range of the holes formed by laser drilling is limited. If the holes are dense and account for a large proportion, the strength of the electrode itself will decrease, while if the holes are large and sparsely distributed, the air permeability is poor, and the air permeability is only present at the location of the holes.
[0054] Compared with the method of forming pores by using water-soluble sacrificial particles, that is, by dissolving water-soluble particles such as water-soluble salt particles and water-soluble sugar particles in water, the preparation method of the present invention can form a breathable channel perpendicular to the fibers of the conductive fabric. If the pores formed by sacrificial particles such as water-soluble salt particles or water-soluble sugar particles are too dense, the adhesion quality will be reduced. If they are sparse, no breathable channel can be formed, and the water vapor evaporated from the skin cannot flow out smoothly.
[0055] Specifically, the conductive fabric includes one of a silver-plated fabric, a laser-induced graphene fabric and a copper-nickel-plated fabric.
[0056] Conductive fabrics play a role in conducting electricity, so they can collect bioelectricity emitted by organisms. In specific applications, conductive fabrics use silver-plated fabrics, laser-induced graphene fabrics, and copper-nickel-plated fabrics. The conductive fabrics made of the above materials have good electrical conductivity and can accurately capture bioelectricity, thereby achieving accurate collection of biopotential.
[0057] Specifically, one side of the conductive fabric is a weft layer 1, and the other side of the conductive fabric is a warp layer 2. The weft layer 1 of the conductive fabric is in a twill grid shape.
[0058] In a specific embodiment of the present invention, the weft layer 1 fiber is composed of a single silver-plated fiber with a fiber diameter of 35 μm. The warp layer 2 is composed of four converged fibers, and the winding network of the intersection of the warp and the weft constitutes an interlayer electrical conduction path, and also forms a vertical water vapor channel after the water-soluble material coating 3 is dissolved. The conductive fabric with the above structure forms a three-dimensional network structure with a large number of water vapor channels inside, thereby having excellent air permeability.
[0059] Specifically, in step S3, after degassing, the viscous silicone is scraped flat so that the viscous silicone 4 fills the gap between the warp layer 2 and the weft layer 1, and the excess viscous silicone is scraped off so that the liquid surface of the viscous silicone is level with the warp layer 2.
[0060] By adopting the above steps, excessive sticky silicone can be removed to prevent the thickness of the three-dimensional breathable electrode sheet from increasing due to excessive sticky silicone, resulting in an increase in the distance between the conductive fabric and the skin, thereby affecting the detection effect.
[0061] Specifically, the coating density of the water-soluble film-forming material solution is 0.35 to 0.45 L / m 2 .
[0062] By adopting the above coating density, it is possible to avoid excessive water-soluble film-forming material solution, which would result in excessive water-soluble film-forming material solution in the gaps of the conductive fabric, resulting in a reduction in the coating amount of the viscous silica gel and a reduced adhesion effect.
[0063] Specifically, the water-soluble film-forming material solution includes a water-soluble film-forming material and a solvent, the water-soluble film-forming material is dissolved in the solvent, and the concentration of the water-soluble film-forming material is 2.5 to 12.5 wt %;
[0064] The water-soluble film-forming material includes one of hydroxypropyl methylcellulose, polyvinyl pyrrolidone, polyacrylic acid and its salts, gelatin and polyethylene glycol, and the solvent includes one of water and ethanol.
[0065] The water-soluble film-forming material solution is prepared by dissolving the water-soluble film-forming material in a solvent. In a specific embodiment of the present invention, the water-soluble film-forming material powder is placed in 90° C. deionized water and stirred until it is completely dissolved to obtain the water-soluble film-forming material solution.
[0066] The water-soluble film-forming material has good film-forming property and is soluble in water. When the solvent evaporates, a reliable water-soluble material coating 3 can be formed. When placed in water, the water-soluble material coating 3 can be quickly dissolved, thereby increasing the production rate. The solvent is water or ethanol, which can be quickly dried and evaporated, thereby accelerating the film-forming speed.
[0067] Specifically, the viscous silica gel comprises polybutylene terephthalate-adipate copolymer and medical silicone gel, and calculated by mass percentage, the polybutylene terephthalate-adipate copolymer accounts for 10-30% of the total mass of the viscous silica gel.
[0068] The viscous silica gel is mixed with polybutylene terephthalate-adipate copolymer and medical silicone gel, and the polybutylene terephthalate-adipate copolymer accounts for the total mass of the viscous silica gel. In a specific embodiment of the present invention, the polybutylene terephthalate-adipate copolymer is a degradable polyester of BASF, a German chemical company, and the commercial model is Ecofelx-0030; the medical silicone gel is a medical addition-type organic silicone gel, and the commercial model is XY-8060, and the polybutylene terephthalate-adipate copolymer accounts for 10-30% of the total mass of the viscous silica gel.
[0069] The above-mentioned viscous silica gel has good bio-tissue compatibility and adhesion, making the electrode sheet comfortable to wear and reducing the discomfort of the wearer.
[0070] Specifically, in step S5, the temperature of the water in which the solidified conductive fabric is immersed is 95-100° C. The above water temperature can accelerate the dissolution of the water-soluble material coating 3 and improve the dissolution efficiency.
[0071] The present invention also provides a three-dimensional breathable electrode sheet, which is prepared by the above-mentioned method for preparing the three-dimensional breathable electrode sheet.
[0072] The three-dimensional breathable electrode sheet prepared by the preparation method of the three-dimensional breathable electrode sheet has a breathable network structure, which can reduce the occurrence of skin itching, redness, swelling and even allergies during long-term wearing of the user, ensure the bio-tissue compatibility of the electrode sheet, make the electrode sheet comfortable to wear, and reduce the wearer's discomfort.
[0073] The present invention also provides an application of a three-dimensional breathable electrode sheet in a dry ECG electrode, wherein the electrode sheet of the potential sensor is prepared by the above-mentioned method for preparing the three-dimensional breathable electrode sheet.
[0074] The dry ECG electrode prepared by this method has good conductivity, flexibility and biocompatibility, and can be made compatible with existing ECG signal detection systems through an electrode sheet assembly process.
[0075] Example Group A
[0076] Take a 0.2mm thick silver-plated fabric and cut it into a 40mm diameter circle, and prepare a 0.3mm thick lining cloth and cut it into a 40mm diameter circle; place the cut conductive fabric in a plasma cleaning machine and clean it in an oxygen atmosphere at a power of 20W for 120s;
[0077] The polyvinyl alcohol resin powder was stirred in 90°C deionized water until it was completely dissolved to obtain a water-soluble film-forming material solution. The concentration of the water-soluble film-forming material is shown in Table 1. The water-soluble film-forming material solution was stirred at 0.35-0.45 L / m 2The coating density is uniformly coated on one side of the weft layer 1 of the conductive fabric, and the conductive fabric is placed in a drying oven at 30° C. for 15 minutes; a water-soluble material coating 3 is formed on one side of the conductive fabric to obtain a conductive fabric with a film;
[0078] The viscous silica gel 4 is coated on one side of the warp layer 2 of the film-bearing conductive fabric, and degassing is performed so that the viscous silica gel 4 fills the gaps in the conductive fabric; the viscous silica gel 4 is placed in a drying oven at 60° C. for heating and drying for 1 hour to obtain a silica gel conductive fabric; the components of the viscous silica gel 4 are shown in Table 1;
[0079] The mesh-shaped lining cloth 5 is pressed on the other side surface of the silicone conductive fabric; curing and drying are performed to completely cure the silicone to obtain a cured conductive fabric;
[0080] The cured conductive fabric is immersed in water at 50° C. to completely dissolve the water-soluble material coating 3, and a three-dimensional breathable electrode sheet is obtained after drying.
[0081] Table 1-Specific parameters
[0082]
[0083] Performance Testing
[0084] The three-dimensional breathable electrode sheets, ordinary conductive fabrics and commercial 3M gel electrode foam adhesive obtained in Examples 1 to 4, Example 6 and Example 7 were subjected to an electrode sheet air permeability test, and the three-dimensional breathable electrode sheets, ordinary conductive fabrics and commercial 3M gel electrode foam adhesive obtained in Examples 1 to 7 were subjected to a skin affinity test.
[0085] The steps of the electrode sheet air permeability test include: using a sample bottle with an opening diameter of 11.5 mm, injecting 5 g of deionized water, cutting a sample of appropriate size and completely covering the opening of the sample bottle with the sample, tightening the conductive fabric group with a rubber band, and then measuring the overall mass with a precision balance; then placing the whole in a blast drying oven at 36°C, measuring the overall mass with a precision balance every 30 minutes and calculating the water evaporation rate, and continuing for 3 hours. The results are shown in Table Figure 5 .
[0086] according to Figure 5 It can be seen that the water evaporation rate of the electrode sheet is lower than that of ordinary conductive fabrics, but higher than that of commercial 3M gel electrode foam adhesive. Because the thickness of the foam adhesive is 1mm, and the thickness of the electrode sheet in Example Group A is about 0.6mm, and the adhesive coating of the foam adhesive almost covers the mesh of the foam layer, resulting in poor air permeability. The electrode sheet structure characterization part also shows the effect of the PVA solution concentration on the three-dimensional grid pores of the electrode. The air permeability of Example Group A is theoretically enhanced with the increase of the PVA solution concentration.
[0087] The steps of the skin affinity test include: using fresh pork with skin, sticking samples or silver-plated fabrics at appropriate positions, adding a small amount of water to the culture dish holding the pork, wrapping the whole with plastic wrap, placing it in a 4°C refrigerator for 24 hours, taking it out for comparison, and observing the appearance of the pig skin. If the color of the pig skin becomes darker, it means that the skin affinity is poor, and the color is consistent with the area without the sample or silver-plated fabric, it means that the skin affinity is excellent. The results are shown in Table 2.
[0088] Table 2 - Skin affinity test results
[0089]
[0090] The electrode contact impedance test was performed on Example 4, the commercial 3M gel electrode foam adhesive and the conductive fabric laminated with the lining cloth.
[0091] It can be seen from Table 2 that the electrode sheet prepared by the preparation method has good skin affinity.
[0092] The contact impedance test of Example 4, commercial 3M gel electrode foam adhesive and conductive fabric electrode was conducted. The specific steps include: using two copper foils to clamp the electrode sample and pig skin, pasting a vibration motor with a mass of 4g on the copper foil pasted with the electrode, powering the motor and measuring the impedance-time curve under the 30Hz signal between the two copper foils, and using a high-precision force sensor to record the vibration force of the vibration motor in the horizontal uniaxial direction under different voltages. The experiment uses 1V and 1.5V voltages to power the motor, 1V is the minimum starting voltage, and the force sensor output signal is as follows Figure 6 As shown in the figure. The vibration force amplitudes at 1V and 1.5V are approximately 0.2N and 0.8N respectively, and the vibration frequencies are 66Hz and 106Hz respectively. The corresponding impedance change curves are shown in the figure below. Figure 7 , Figure 8 shown.
[0093] according to Figure 7 and Figure 8 It can be seen that the contact impedance of Example 4 and the commercial 3M gel electrode foam adhesive is stable under 1V power supply, while the silver-plated fabric electrode without an adhesive layer has shown a large degree of contact impedance jitter. When powered at 1.5V, the contact impedance of the commercial 3M gel electrode foam adhesive remains stable, while the contact impedance of Example 4 shows visible jitter, but the contact impedance jitter level of both is an order of magnitude smaller than that of the silver-plated fabric at this time. The contact impedance jitter of the silver-plated fabric represents that the connection between the electrode sheet and the contact surface is unreliable, which can easily lead to motion artifact interference or even poor contact.
[0094] Example 4, commercial 3M gel electrode foam adhesive and conductive fabric laminated with lining cloth are prepared into a potential sensor, wherein the electrode sheet has an opening on the backing during preparation and uses conductive fabric as the pole ear, the pole ear is in contact with the conductive layer, the conductive layer is in contact with the silver-plated sewing thread, and the conductive sewing thread transmits the electrical signal to the Ag-AgCl electrode and the steel buckle. The conductors are bonded with food-grade silicone, and the contact is conductive through bonding stress. Food silicone is used to bond the non-conductive functional layers on the outer circle. The flexible tray is made by using silicone mold on the corresponding 3D printing mold. The diameter of the potential sensor is 40 mm, and the thickness of the potential sensor without the steel buckle is 5 mm. The potential sensor prepared with Example 4 and commercial 3M gel electrode foam adhesive is applied to an electrocardiograph; the electrode output is as follows Fig. 9 As shown, the upper part is the waveform collected by the commercial 3M gel electrode foam adhesive, and the lower part is the waveform collected by the electrode of Example 4.
[0095] By comparison, it can be seen that the signal waveform of each lead has an obvious PQRST peak, and the waveform is basically consistent with the waveform of the commercial 3M gel electrode foam adhesive, and the amplitude of each lead is also comparable to the amplitude of the commercial 3M gel electrode foam adhesive. The ECG acquisition performance of the electrode in Example 4 is close to that of the commercial 3M gel electrode foam adhesive, and can better reflect the actual ECG waveform.
[0096] The potential sensor of Example 4, commercial 3M gel electrode foam adhesive and conductive fabric with lining cloth pressed together were prepared and applied to the five-lead dynamic electrocardiogram acquisition device. The output of leads I, II, and V4 was measured in the walking state. The results are shown in FIG. Fig.10 ; Measure the output of leads I, II, and V4 in the jogging state. The results are shown in Fig.11 .
[0097] pass Fig.10 and Fig.11 It can be seen that the signal quality of Example 4 is better than that of the 3M electrode and the silver-plated fabric.
[0098] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific embodiments of the present invention without creative work, and these equivalent variations or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A method for preparing a three-dimensional gas-permeable electrode sheet, characterized in that: The following steps are involved: S1. Cleaning the conductive fabric; S2, uniformly coating the water-soluble film-forming material solution on one side of the conductive fabric, and drying the solution to form a water-soluble material coating on one side of the conductive fabric, thereby obtaining a conductive fabric with a film; S3, coating the sticky silica gel on the other side of the conductive fabric with the film, and degassing, so that the sticky silica gel fills the gaps in the conductive fabric; heating and drying, to obtain the silica gel conductive fabric; S4, pressing a mesh lining cloth on the other side surface of the silicone conductive fabric; performing curing and drying to completely cure the silicone to obtain a cured conductive fabric; S5. Soak the cured conductive fabric in water to completely dissolve the water-soluble material coating, and obtain a three-dimensional breathable electrode sheet after drying.
2. The method for preparing a three-dimensional gas-permeable electrode sheet according to claim 1, characterized in that: The conductive fabric includes one of a silver-plated fabric, a laser-induced graphene fabric and a copper-nickel-plated fabric.
3. The method for preparing a three-dimensional gas-permeable electrode sheet according to claim 2, characterized in that: One side of the conductive fabric is a weft layer, and the other side of the conductive fabric is a warp layer. The weft layer of the conductive fabric is in a twill grid shape.
4. The method for preparing a three-dimensional gas-permeable electrode sheet according to claim 3, characterized in that: In step S3, after degassing, the viscous silicone is scraped flat so that the viscous silicone fills the gaps between the warp layer and the weft layer, and excess viscous silicone is scraped off so that the liquid surface of the viscous silicone is flush with the warp layer.
5. The method for preparing a three-dimensional gas-permeable electrode sheet according to claim 1, characterized in that: The coating density of the water-soluble film-forming material solution is 0.35 to 0.45 L / m 2 .
6. The method for preparing a three-dimensional gas-permeable electrode sheet according to claim 1, characterized in that: The water-soluble film-forming material solution comprises a water-soluble film-forming material and a solvent, the water-soluble film-forming material is dissolved in the solvent, and the concentration of the water-soluble film-forming material is 2.5 to 12.5 wt %; The water-soluble film-forming material includes one of hydroxypropyl methylcellulose, polyvinyl pyrrolidone, polyacrylic acid and its salts, gelatin and polyethylene glycol, and the solvent includes one of water and ethanol.
7. The method for preparing a three-dimensional gas-permeable electrode sheet according to claim 1, characterized in that: The viscous silica gel comprises polybutylene terephthalate-adipate copolymer and medical silicone gel. Calculated by mass percentage, the polybutylene terephthalate-adipate copolymer accounts for 10-30% of the total mass of the viscous silica gel.
8. The method for preparing a three-dimensional gas-permeable electrode sheet according to claim 1, characterized in that: In the step S5, the temperature of the water in which the cured conductive fabric is immersed is 95-100°C.
9. A three-dimensional breathable electrode sheet, characterized in that: The three-dimensional gas permeable electrode sheet is prepared by the preparation method of the three-dimensional gas permeable electrode sheet according to any one of claims 1 to 8.
10. Application of a three-dimensional breathable electrode sheet in a dry ECG electrode, characterized in that: The electrode sheet of the potential sensor is prepared by the preparation method of the three-dimensional gas-permeable electrode sheet according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of spinning electrode used for testing electrocardiosignal
CN103462602A
Novel sweat-absorbent fabric electrode
CN107198519A
Fabric electrocardio-electrode and preparation method and application thereof
CN114903488A
Flexible bioelectric dry electrode and preparation method and application thereof
CN114947865A
Integrally-formed electrocardio-garment based on fiber-based fabric electrocardio-electrode and preparation method of integrally-formed electrocardio-garment
CN117158978A